Study on the Role of Fish-Derived Bioactive Compounds in Cancer Therapy: A Molecular Perspective (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Marine and freshwater ecosystems have been recognized as rich sources of pharmacologically active compounds, particularly those with anticancer properties. This study explores the molecular mechanisms and therapeutic potential of fish-derived bioactive molecules, including peptides, alkaloids, and polysaccharides, in cancer treatment. The results demonstrate that these compounds exert strong cytotoxic effects on various cancer cell lines, with alkaloids showing the highest potency against HT-29 colon cancer cells and peptides effectively targeting MCF- 7 breast cancer cells. Gene expression and Western blot analyses reveal significant upregulation of pro-apoptotic markers (Bax, Caspase-3, p53) and downregulation of anti-apoptotic (Bcl-2) and angiogenic markers (VEGF, MMP-9), confirming their ability to induce apoptosis and inhibit tumor angiogenesis. DNA fragmentation analysis further supports their role in cancer cell death by demonstrating increased DNA damage in treated cells. The statistical evaluation confirms the high significance of these findings, underscoring their therapeutic relevance. While challenges remain in large-scale extraction, stability, and pharmacokinetics, these compounds hold immense promise for future drug development. By integrating fish-derived bioactives into targeted cancer therapies, researchers can develop novel, less toxic treatment strategies that effectively combat drug-resistant tumors, paving the way for marine-based cancer therapeutics.